2010
DOI: 10.1002/cncr.25355
|View full text |Cite
|
Sign up to set email alerts
|

The expanding melanoma burden in California hispanics

Abstract: BACKGROUND:The incidence patterns and socioeconomic distribution of cutaneous melanoma among Hispanics are poorly understood. METHODS: The authors obtained population-based incidence data for all Hispanic and nonHispanic white (NHW) patients who were diagnosed with invasive cutaneous melanoma from 1988 to 2007 in California. By using a neighborhood-level measure of socioeconomic status (SES), the variables investigated included incidence, thickness at diagnosis, histologic subtype, anatomic site, and the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 46 publications
2
58
0
Order By: Relevance
“…While Blacks and Hispanics were more likely to present with extremities melanomas and to experience a longer LOS and a higher cost. The observed higher prevalence of extremities melanoma in minorities is congruent with the established higher incidence of peripheral and acral melanoma in Black and Hispanics [13, 30, 33, 36]. In the multivariate model, there was no significant disparity in nodal metastasis among the different racial groups.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…While Blacks and Hispanics were more likely to present with extremities melanomas and to experience a longer LOS and a higher cost. The observed higher prevalence of extremities melanoma in minorities is congruent with the established higher incidence of peripheral and acral melanoma in Black and Hispanics [13, 30, 33, 36]. In the multivariate model, there was no significant disparity in nodal metastasis among the different racial groups.…”
Section: Discussionsupporting
confidence: 67%
“…The socioeconomic status association with melanoma has been explored frequently with an effort to explain the racial disparities in melanoma outcomes. Most studies agree that melanoma risk is higher in population of high socioeconomic status, while a worse prognosis is more relevant in populations of low socioeconomic status [5, 11, 16, 29, 33]. There is some evidence that the differences in patient outcomes are associated with the type of health care delivery system in which they are enrolled [14, 15, 35].…”
Section: Discussionmentioning
confidence: 99%
“…R ecently, malignant melanoma (MM) has become a subject of major interest due to an increasing incidence and high morbidity and mortality rates [1][2][3][4][5][6] . Although this tumor represents only 4-5% of the skin cancers, it is the main cause of death related to skin malignancies, due to late diagnosis and high potential of distant metastases.…”
Section: Melanoma Maligno Constituye Una Importante Preocupación Debimentioning
confidence: 99%
“…Although this tumor represents only 4-5% of the skin cancers, it is the main cause of death related to skin malignancies, due to late diagnosis and high potential of distant metastases. Foot and nail are uncommon sites (3-15%), with poor prognosis and high lethality [1][2][3][4][5][6] . Worth of note, a study of 4,607 Hispanic Californians with MM showed thicker tumors, in a late stage at diagnosis, with metastases and poor outcomes 4 .…”
Section: Melanoma Maligno Constituye Una Importante Preocupación Debimentioning
confidence: 99%
See 1 more Smart Citation